VARIATIONS OF CADMIUM LEVELS IN MOOSE TISSUES FROM THE ABITIBI-TÉMISCAMINGUE REGION - Paré, Marcel; Prairie, Robert; Speyer, Menno (Lakehead University, 1999)
In the fall of 1986. 1,147 samples of kidney, liver, and skeletal muscle of 508 moose (Alces alces) and 38 black bears (Ursus americana) from Abitibi-Témiscamingue in western Québec were analyzed. The cadmium levels measured in the liver and kidney samples made it possible to establish the distribution of cadmium in the regional environment. As has seen shown in other studies, cadmium concentrations in these tissues increases with age, can differ according to sex, and can vary greatly according to the area sampled. Three homogenous contamination sectors were identified: the highest contamination unit is directly inflected by a copper smelter. The cadmium levels in Abitibi-Témiscamingue are the highest measured in Québec and elsewhere: the mean value (μg/g) ± SE (range) was 72.4 ± 3.9 (0.0 - 440.1) in the kidneys, 11.2 ± 0.7 (0.4 - 232.1) in the liver, and 0.023 ± 0.007 (0.000 - 1.930) in the muscles. In the high contamination zone, we had analyses done on liver and kidney samples from 38 black bears. The cadmium concentrations turned out to be higher than those in moose, namely 282.6 ± 126.0 (55.6 - 572.2) in the kidneys and 22.6 ± 17.6 (2.1 - 70.9) in the liver. A sulfuric acid plant has been in operation at the copper smelter since 1989, which has reduced cadmium emissions significantly. In the fall of 1995, we had analyses done on kidney samples of 35 moose calves from 2 different contamination sectors to make a comparison with the 1986 results. The average cadmium concentrations did not vary during this period in the 2 different sectors. We propose an inexpensive, yet efficient method that would allow us to monitor changes in contamination levels over time.